THE GAS PIPELINES: A GAME OF CASPIAN PATIENCE - SMIRNOV, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2007)
We all know that the European gas reserves in the North Sea are rapidly depleting. This means that the leading countries of Western Europe and some of the East European countries will have to look for fuel elsewhere. Scared by the Russian-Ukrainian “gas squabbles” they are actively seeking alternative sources. Poland went as far as suggesting that the EU should create an energy pact (patterned on NATO) under which all members would pledge to help those in their ranks that need urgent support. So far, the idea has not gained support.Today, new pipelines from the Caspian area, the Middle East, and North Africa might be built; new marine terminals for tankers carrying liquefied gas from the Persian Gulf are also needed. The commissioned North African gas fields cannot cover Europe’s gas needs. The Middle East cannot be described as a stable gas supplier; it also prefers to sell its liquefied gas to Southeast Asia. In this context, the Caspian looks like the best possible option.Practically all the projects look at Central Asia and Azerbaijan as the main gas suppliers; so far little has been said about the projects’ possible economic efficiency. It is still much more important to attract attention to one’s own country, to raise a “political wave,” and to scare away potential rivals. The Europeans are working on the Nabucco project (a gas pipeline that will go from the southern part of the Caspian, via Turkey to Southeast Europe. It will end in Baumgarten in Austria). The plan is far from complete: investments, gas sources, and transportation tariffs have not been discussed, no national companies have been set up for engaging in construction; preliminary works have not yet begun.The “gas projects on paper” seem to pursue purely strategic aims. The West and Russia are fully aware that until the Caspian’s legal status has been fixed all talks, let alone agreements, on extracting anything on the Caspian shelf or laying pipelines on its bed will remain futile deliberations measured in mega- and giga-bites of political wishful thinking rather than in cubic meters and dollars. This and the fact that the local proven gas reserves will not be enough to fill all the pipelines are successfully ignored.